(untitled) (Medical Forum Monthly, 2024)
Objective: to examine the association between artificially sweetened beverage (ASB) consumption and obesity/overweight in a large, nationally representative sample of UK children. Study Design: Observational / cross-section study. Place and Duration of Study: This study was conducted at Avicenna Medical & Dental College, Lahore December 2017 to February 2018. Materials and Methods: Data came from the UK Millennium Cohort Study sweep 5. The sample included 13,287 children aged 10-12 years. Multinomial regression models were run to examine the associations between ASB consumption and obesity, after adjusting for socio-demographic factors and physical activity. Results: A significant association between ASB consumption and obesity was detected in multinomial regression models. After adjusting for socio-demographic factors and physical activity, children who frequently consumed ASB had a 59% (CI: 1.36-1.85) increased relative risk of being overweight and a 2.39 times (CI: 1.82-3.13) greater relative risk of being obese than those with no ASB consumption. Conclusion: ASB consumption was found to be significantly associated with obesity. Further research is needed on the role of added sugars and artificial sweeteners in beverages for childhood obesity. A further comprehensive research with intervention design is recommended.